EVALUASI PERBAIKAN PONDASI KONDUIT DENGAN METODE GROUTING - Andy Rosyulianta Irfan; Mochamad solikin; Sri Sunarjono (Politeknik Negeri Semarang, 2022)
The Tugu Dam is one of the National Strategic Projects located in Trenggalek, East Java. Dam construction is an old practice, so history of dam shows great innovations in engineering. The innovations are not only for foundation design, but for foundation failure repairing. In the conduit of the Tugu dam, there is displacement as far as 20 mm - 60 mm. The alternative foundation failure repairing is grouting. The purpose of this study is to identify problems in the foundation failure of Conduit Tugu Dam and to evaluate the effectiveness of grouting based on the lugeon value and displacement value in the simulation by software. The results of the investigation that obtained a colovial layer as deep as 15-28 (m) in the displacement. The Lugeon Value area by testing the water pressure is 3,54 – 104,13. After the grouting work is done and the water pressure test is carried out, the Lugeon value on the Check Hole is 1,01 – 4,95 so that the grouting effectiveness is 75% (good category). The results using sigma/w show that displacement without using grout is -0,394 (m) alternative 1 is -0,027 (m), alternative 2 is -0,051(m), alternative 3 is -0,034 (m) and alternative 4 is -0,026 (m).